Psychometric validation of the Italian version of the Reported and Intended Behaviour Scale (RIBS). (30th July 2015) - Pingani, L.; Evans-Lacko, S.; Luciano, M.; Del Vecchio, V.; Ferrari, S.; Sampogna, G.; Croci, I.; Del Fatto, T.; Rigatelli, M.; Fiorillo, A.
Abstract : Background: Many instruments have been developed and validated to assess the stigma associated with mental disorders and its various domains across different populations. To our knowledge, the Reported and Intended Behaviour Scale (RIBS) is the only validated questionnaire to analyse the presence of reported and intended stigmatising/discriminatory behaviours towards people with mental health problems in the general population. The aims of the study presented herein are to translate and validate the RIBS in Italian language and to adapt it to the Italian socio-cultural background (RIBS-I). Method: The RIBS considers reported and intended behaviours across four different domains: (1) living with, (2) working with, (3) living nearby and (4) continuing a relationship with someone with a mental health problem. The validation process included four phases: (1) translation/back translation of the questionnaire from English to Italian and vice versa; (2, 3) face validity and reliability of RIBS-I; (4) description of model fit through confirmatory factor analysis. The questionnaire was administered to a sample of the general public via distribution in public places such as shopping centres, markets, squares, cinemas and other gathering places. Questionnaires were administered by trained mental health professionals. Results: A total of 447 lay respondents were recruited. The mean age was 38.08 (s.d. = ±14.74) years. Fifty-seven per cent of the sample ( n = 257) were female. The Cronbach alpha of RIBS-I was 0.83. All indices of model fit were above the reference values: Goodness of Fit Index (GFI) = 0.987 (GFI > 0.9); Adjusted Goodness of Fit Index (AGFI) = 0.975 (AGFI > 0.9); Comparative Fit Index (CFI) = 0.994 (CFI > 0.9); and Root-Mean-Square Error of Approximation (RMSEA) = 0.023 (RMSEA < 0.05). The χ 2 = 23.60 (df = 19; p = 0.21) and χ 2 /df = 1.24 supported the model. Conclusions: The RIBS-I demonstrated good psychometric properties and it can be considered a useful tool to: (1) assess stigmatising (actual or potential) behaviours in the general population; (2) test the efficacy of anti-stigma campaigns and actions; (3) design further studies to better understand the relationship between the three different components of stigmatisation: knowledge, attitudes and behaviours.